2022
DOI: 10.11648/j.ajese.20220601.12
|View full text |Cite
|
Sign up to set email alerts
|

Urban Air Pollution Caused of Particulate Matter and Lead in the City of Chittagong-Bangladesh

Abstract: Chittagong city is one of the largest and commercial cities of Bangladesh. Many industries are continuously producing particulate matters by their daily activity. Air pollution due to the PM has significant effects on asthma, allergy and other respiratory diseases. There is a great need to implement control measures in most of the megacities of the world to improve air quality and hence protect public health. Like many megacities in the world the ambient air quality of Chittagong is also being deteriorated day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
1
2
Order By: Relevance
“…In 2021, the studied data showed that the average concentration of particulate matter (PM2.5) was 80.15, 83.14, 83.06, 67.03, 68.74, 69.20 and 69.17 µg/m 3 for the WASA Circle, the GEC Circle, Proborthak Circle, Chawkbazar Circle, Alongkar Circle, New Market Circle, Oxygen Circle, respectively, in the city of Chittagong. The previously established data was too high than in the current study [26].…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…In 2021, the studied data showed that the average concentration of particulate matter (PM2.5) was 80.15, 83.14, 83.06, 67.03, 68.74, 69.20 and 69.17 µg/m 3 for the WASA Circle, the GEC Circle, Proborthak Circle, Chawkbazar Circle, Alongkar Circle, New Market Circle, Oxygen Circle, respectively, in the city of Chittagong. The previously established data was too high than in the current study [26].…”
Section: Resultscontrasting
confidence: 84%
“…Circle, Proborthak Circle, Chawkbazar Circle, Alongkar Circle, New Market Circle, Oxygen Circle, respectively, in the city of Chittagong. The previously established data was too high than in the current study [26].…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation